Efficient degradation of refractory organic contaminants by zero-valent copper/hydroxylamine/peroxymonosulfate process. (December 2019) - Chi, Huizhong; He, Xu; Zhang, Jianqiao; Ma, Jun
Abstract: Degradation of naproxen, bisphenol S and ibuprofen in a hydroxylamine enhanced zero-valent copper (Cu 0 ) catalyzed peroxymonosulfate system was investigated for the first time. We found that hydroxylamine addition accelerated the reduction of Cu 2+ to Cu + as well as the corrosion of Cu 0, and environmental friendly gas nitrogen was the main product of hydroxylamine. Additionally, hydroxyl radical and sulfate radical were identified to be the dominant reaction species by competitive experiments. The degradation of naproxen, bisphenol S and ibuprofen kept highly efficient in the pH range of 3.0–7.0 in Cu 0 /hydroxylamine/peroxymonosulfate process, with their degradation products identified by HPLC-MS, which showed that Cu 0 /hydroxylamine/peroxymonosulfate system could be an alternative to remove non-steroidal antiinflammatory drugs or plasticizers in wastewater. Furthermore, the effects of Cu 0, hydroxylamine and peroxymonosulfate dosage were studied and optimized by a BBD based response surface model. This study provided a method to solve the disadvantages of Cu 0 /peroxymonosulfate systems, and gave a promising method to enhance the efficiencies of ZVMs activated system such as iron, cobalt and copper. Highlights: Degradation of naproxen, ibuprofen and bisphenol S in Cu 0 /HA/PMS system and their degradation intermediates were obtained. HA enhanced the degradation efficiencies of Cu 0 /PMS system by accelerating the reduction of Cu 2+ and the corrosion of Cu 0 . Hydroxyl radicals and sulfate radicals were the dominant reaction species in Cu 0 /HA/PMS system. The condition of Cu 0 /HA/PMS system was optimized using RSM model.